Co oxide nanostructures for electrocatalytic water-oxidation: effects of dimensionality and related properties. Issue 18 (1st May 2018) - Gupta, S.; Yadav, A.; Bhartiya, S.; Singh, M. K.; Miotello, A.; Sarkar, A.; Patel, N.
Abstract : Single-dimensional nanostructures of Co oxide: a unique opportunity to understand the role of different material-related parameters in water oxidation. Abstract : A facile hydrothermal synthesis route was explored to obtain various nanostructures of Co oxide for applications in electrocatalytic water-splitting. The effect of reaction time and metal precursor ions on the morphology of synthesized nanostructures was studied in detail with the aid of a scanning electron microscope. By systematic optimization of the synthesis parameters, Co oxide nanostructures with single dimensionality were obtained in the form of 0D nanoparticles (NPs), 1D nanowires (NWs), 2D nanosheets (NSs) and 3D nanocrystals (NCs). The effectiveness of the developed nanostructures towards oxygen evolution reaction (OER) was studied and a promising OER activity was recorded for all the samples. Amongst all the developed catalysts, Co(OH)2 NPs showed the lowest overpotential of 339 mV to achieve a current density of 10 mA cm −2, which is even lower than that of noble-metal oxides such as the commercial RuO2 catalyst (370 mV). The specific effect of different parameters such as BET surface area, phase, crystallographic orientation of surface lattice planes, electroactive surface area and surface active species on the OER performance was studied. It was found that the Co3 O4 phase is more active for the OER, compared to the Co(OH)2 phase. However, Co(OH)2 NPs showed the best OER performance owing to their higher BET surface area, thereby underlining the significance of the catalyst surface area. The effect of the number of active surface atoms was demonstrated by estimating the electroactive surface area of all Co3 O4 nanostructures. It was also shown that the formation of CoO2 species (Co (IV) ) on the surface is more beneficial for the OER as compared to the formation of CoOOH species (Co (III) ). Finally, the robustness of the developed Co3 O4 nanostructures was established by performing a recycling test for the OER (1000 cycles) and the observed change in the catalytic activity was correlated with morphological variation.